2018
DOI: 10.15252/embj.201798308
|View full text |Cite
|
Sign up to set email alerts
|

p62 filaments capture and present ubiquitinated cargos for autophagy

Abstract: The removal of misfolded, ubiquitinated proteins is an essential part of the protein quality control. The ubiquitin‐proteasome system (UPS) and autophagy are two interconnected pathways that mediate the degradation of such proteins. During autophagy, ubiquitinated proteins are clustered in a p62‐dependent manner and are subsequently engulfed by autophagosomes. However, the nature of the protein substrates targeted for autophagy is unclear. Here, we developed a reconstituted system using purified components and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
358
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(399 citation statements)
references
References 74 publications
17
358
1
Order By: Relevance
“…In agreement with previous in vitro observations [23], NBR1 facilitated the formation of p62-liquid bodies in cells (Fig 1). How does NBR1 promote phase separation of p62?…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous in vitro observations [23], NBR1 facilitated the formation of p62-liquid bodies in cells (Fig 1). How does NBR1 promote phase separation of p62?…”
Section: Discussionsupporting
confidence: 93%
“…NBR1 enhances the protein levels of p62 partially independent on Nrf2. is required for phase separation [6,23]. Thus, it is likely that the increase in the phosphorylation states of p62 produced by NBR1 positively influences the formation of p62 bodies.…”
Section: Discussionmentioning
confidence: 99%
“…2A). However, two recent publications showed that the structures formed by SQSTM1 undergo phase-separation and have liquid-like properties that depend on the presence of ubiquitin chains (Sun et al, 2018;Zaffagnini et al, 2018) (Fig. 2B).…”
Section: Box 1 Selective Autophagy Is Mediated By a Several Receptormentioning
confidence: 94%
“…A recent report found that KEAP1/ CUL3 ubiquitylates p62 on its ubiquitin-associated domain (UBA) and that this interaction is crucial for the recruitment of p62 into the autophagosome (123,124). Furthermore, a role for p62 and polyubiquitin in the formation of phase-separated autophagic intermediates has been recently defined (125)(126)(127). Conformationally strained KEAP1 due to ANCHOR mutations may result in decreased or absent p62 ubiquitylation, preventing tethering to LC3 for autophagosome formation and maturation.…”
Section: Parentalmentioning
confidence: 99%